Effect of Surface Finish Reflectance on Energy Consumed by Lighting - Alkhalidi Ammar (Sciendo, 2021)
Efforts from both spatial and energy engineers were conceived in order to reduce the total running costs of electric consumption in buildings. An often-overlooked energy and money saving opportunity for the built environment lies in lighting. This study investigates the effect of room interior finish on electrical lighting energy consumption. Walls, ceiling, and floor finish, in accordance to light reflectance values, were taken at low reflectance model (LRM), medium reflectance model (MRM), and high reflectance model (HRM). Various occupied spaces were classified in accordance to physical dimensions and capacity in order to cover a wide range of space usage and standard illuminance requirements. It was found that the HRM reduced power consumption in lighting by about 40.62 % compared to the LRM in the case for medium museum halls, with energy saved rating at about 2.32 GWh annually; other occupied spaces show a saving potential between 22.00 % and 40.00 %.